Alaththi Bama :Traditional Ritual Performed by Vedda Woman for Katharagama Deity - Ananda, T.; Nahallage, C. (ICSS 2016, 2016)
Attached

R uhunu M aha K atharagam a D evalaya is a m ulti-ethnic and religious place dedicated to K atharagam a deity w ho is also considered as a one o f greatest spiritual ancestor) Na Yaka (w orshiped by V edda people. His second w ife w as V alli A m m a believed to be an adopted daughter o f a V edda C hief; N anda .A laththi B am a ritual is perform ed by 12 V edda w om en descended by V alli A m m a linage as for blessing o f K atharagam a deity .This study w as aim ed to discover the present status o f this ritualistic perform ance .D ata w as gathered through interview s conducted w ith 6 A laththi A m m a w arn )A laththi M others .(A lththi ritual is perjured before the M uruthan offering )Rice m ade w ith pum pkin, honey e t c - . M uruthan offering is done for three tim es in a day at 4.30 am , 10.30 am , and at 6.30 p m except Saturdays .(On Saturdays A laththi M others bring w ater for )Nanumura Mangalyaya (a w ishig cerem ony in D evalaya from M anik R iver and w ithal traditionally they have assigned to participate to devala processions .King Dutugamunu) 1st century BC (has assigned 8 A laththi m others to pound paddy to get rice for M uruthan offering .Eight o f them accom panying for paddy pounding, around a stone m ortar w ith pestle, called wata wee ketima .Before the M uruthan offering A laththi m others enter in to the devalaya from the right side door holding an unlighted oil lam p w hich w as kept o n the stairs o f the devalaya by kapum ahaththaya) P riest .(Then A lathti m others w orship K atharagam a deity and light the oil lam p and perform their ritual w hile m urm uring their secret blessing stanza .N ext they perform this ritual again in the W ata P ila )In the back side o f the D evalaya .(They dressed up w ith special traditional dress called kam baya )cam boy( w hich is represented there V edda lineage .The leader o f A laththi M others is called as G urunnanse) Teacher( and their duty is m atrilineally descended) goes from m other to daughter .(King D utugam unu's period they have given rice for their duty .Later Rs. 2.85 and at present as a com m on allow ance they receive R s.5000 p er m onth .Apart from their ritualistic life they are having social and fam ily life differing from the H indu devadasi concept )Fem ale servant o f the deity /N au tch girl .(Their m onthly incom e is less than Rs. 10000 w hich is not enough to m aintain their fam ilies .D iffering from early days at present they have confronted m any social and econom ic problem s .Eldest A laththi m other have been perform ing this ritual for 50 years w hich she has started it in h er 2 0 's .Though she has devoted h er entire life for the K atharagam a deity still she have not given considerable gratitude from deities as w ell as from responsible governing bodies .Even though they are having difficulties at present, faithfulness to the K atharagam a deity has been the m ajor reason o f continuation their duty as A laththi M others
Keywords: Alaththi Ritual; Alaththi Amma; Katharagama Deity; Vedda; Indigenous People